Meningkatkan Kinerja Keuangan dan Keberlanjutan Melalui Penerapan E-Commerce dan Media Sosial di Kalangan Usaha Kecil dan Menengah (UKM) - Utami, Hastin Tri; Lestari, Puji; Herwiyanti, Eliada; Praptapa, Agung (AKTSAR: Jurnal Akuntansi Syariah, 2025)
SMEs contribute 61.1% to Indonesia's GDP and employ over 97% of the workforce, yet only 30% last more than five years with sustainable practices. This study aims to examine the impact of e-commerce and social media adoption on SME sustainability, with financial performance as a mediating variable. A quantitative approach using PLS-SEM was conducted on traditional food SMEs in Banyumas. The results indicate that e-commerce adoption significantly affects financial performance (p=0.042), and financial performance significantly affects sustainability (p=0.015). However, no significant mediation effect was found. The GoF value of 0.337 indicates a moderate model fit. While digitalization enhances financial outcomes, its effect on sustainability is not automatic without strong internal capacity.